Just Academic Mobilities in an Unjust World - Sultana, Farhana (ACME, 2024)
Addressing academic mobilities in a time of climate breakdown requires a transformation in social values, behaviors, and systems. Our related task is twofold. First, scholars must foster knowledge production and circulation that 1) challenge a status quo that stems from colonial, capitalist, and racist histories and 2) are consistent with an inclusive, equitable, and low-impact academy. Second, we must strive for just geographies in an unjust world of climate, socioecological, and academic disparities. Such goals necessitate working for far-reaching changes within academic institutions as well as for systemic change in the broader world.